Structural Engineering of the Multilayer Vacuum Arc Nitride Coatings Based on Ti, Cr, Mo and Zr - Sobol, O. V.; Postelnyk, A. A.; Meylekhov, A. A.; Andreev, A. A.; Stolbovoy, V. A.; Gorban, V. F. (Sumy State University, 2017)
The possibilities of structural engineering of multi-period vacuum-arc coatings based on nitrides of transition metals Ti, Cr, Mo, and Zr have been investigated by structural studies (X-ray diffraction and electron microscopy) in combination with measurement of hardness by indentation. The formation of phases with a cubic crystal lattice under nonequilibrium conditions under vacuum arc method of production. The supply of a negative bias potential of – 200V in mononitrides leads to the predominant formation of texture of crystallites with the [111] axis. The introduction of thin (about 10 nm) metal layers leads to a decrease in texture perfection [111] and texture formation [100]. This effect is associated with a change in the stress-strain state of nitride layers. It is determined that the composite multiperiod coatings (Me1N/Me2N)/(Me1/Me2) have a greater hardness and greater resistance compared to MeN/Me. For a multiperiod system with damping metal layers – (ZrN/CrN)/(Zr/Cr), superhard coatings with a hardness of 46 GPa were obtained.

Методами структурних досліджень (рентгенівська дифракція і електронна мікроскопія) в поєднанні з вимірюванням твердості індентуванням вивчені можливості структурної інженерії багатоперіодних вакуумно-дугових покриттів на основі нітридів перехідних металів Ti, Cr, Mo і Zr. Встановлено формування фаз з кубічною кристалічною решіткою в нерівноважних умовах при вакуумно-дуговому методі отримання. Подача негативного потенціалу зсуву -200В в мононітридах призводить до переважного утворення текстури кристалітів з віссю [111]. Введення тонких (близько 10 нм) металевих прошарків призводить до зменшення досконалості текстури [111] і формування текстури [100]. Цей ефект пов'язується зі зміною напружено-деформованого стану нітридних шарів. Визначено, що композиційні багатоперіодні покриття (Me1N/Me2N)/(Me1/Me2) мають високу твердість і високу стійкість в порівнянні з MeN/Me. Для багатоперіодної системи з демпфірувальними металевими шарами - (ZrN/CrN)/(Zr/Cr), отримані надтверді покриття з твердістю 46 ГПа.
Структурна інженерія багатошарових вакуумно-дугових нітридних покриттів на основі Ti, Cr, Mo і Zr
Keywords: vacuum-arc method; multiperiod coatings; structural engineering; stress state; hardness; strength; твердість; міцність; напружений стан; багатоперіодні покриття; рентгенівська дифракція; електронна мікроскопія